Iridium Oxide pH Microsensor Based on Stainless Steel Wire for pH Mapping on Metal Surface - Khalid, Muhamad Fazillah (IRC, 2016)
The pH sensors have been widely used and can be found in biomedical, agriculture, food processing industries as well as engineering material. This kind of pH sensors which are primarily made of glass electrode. In term of sensitivity, glass electrode pH sensors have quite good response. For the strength, glass electrode pH sensors are not the ideal instruments to be used in multi field due to its fragility. As an alternative of conventional glass electrode pH sensor, new type of pH sensors which based on iridium oxide and stainless steel is a good solution. Conventional glass electrode pH sensors already at its own performance but introducing iridium oxide can significantly improve the dynamic property